Pengaruh Logika Institusi, Indikator Kinerja Utama, dan Partisipasi Anggaran terhadap Kinerja Institusional - Robbani, Auliya Akbar; Ferina, Ika Sasti; Kartasari, Shelly Febriana (Owner : Riset dan Jurnal Akuntansi, 2024)
The Merdeka Learning Campus Merdeka Program is implemented in tertiary institutions by the government in order to build competent and quality human resources. This program is realized through performance indicators set by the government to improve their institutional performance. The purpose of this study was to determine the effect of institutional logic, key performance indicators, and sentiments on institutional performance. Neo-Institutional Theory in the study of institution and organization underlies this study by explaining theoritically how institusion are formed, changed, and maintained in society. The method used is the Structural Equation Modeling-Partial Least Squares approach. Statistical testing in this study used the smart pls 3.0 application. Respondents who were involved in this study amounted to 237 employees who were employees of Sriwijaya University. The sampling method of this study used purposive sampling. Data collection techniques using a questionnaire. Data analysis was performed using Structural Equation Modeling-Partial Least Squares. The results showed that partially Institutional Logic had an effect on Institutional Performance, Key Performance Indicators had an effect on Institutional Performance, Budget Participation had an effect on Institutional Performance.